1991
DOI: 10.1002/hep.1840130631
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of bile acids by their high-dose infusion into rats

Abstract: We previously reported that high-dose infusion of ursodeoxycholate into rats caused its extensive glucuronidation. In this study, the glucuronidation of various bile acids after high-dose infusion into rats was examined and the effects of coinfusion of bile acids on the glucuronidation of a trace dose of [14C]deoxycholate were also studied. Sixty minutes after infusion of 14C-bile acids at a rate of 1 mumol/min/100 gm, the glucuronidation of the labeled bile acid in the bile was 31%, 15%, 8% and 3% for deoxych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…By contrast, Hayakawa [28] reported that UDC markedly inhibited biliary cefotiam excretion in rats. The reason for this discrepancy may be due to his usage of a high dose of UDC, which we previously reported to cause exten sive glucuronidation of this bile acid [29,30]. Since 3-glyA-LC inhibited biliary CPM excre tion in the present study, UDC glucuronide may have inhibited biliary CPM excretion in his study [28].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…By contrast, Hayakawa [28] reported that UDC markedly inhibited biliary cefotiam excretion in rats. The reason for this discrepancy may be due to his usage of a high dose of UDC, which we previously reported to cause exten sive glucuronidation of this bile acid [29,30]. Since 3-glyA-LC inhibited biliary CPM excre tion in the present study, UDC glucuronide may have inhibited biliary CPM excretion in his study [28].…”
Section: Discussionmentioning
confidence: 67%
“…This possibility may be supported by several reports suggesting the existence of more than two excretory pathways for organic anions ' [15][16][17][18][19][20], In summary, the excretory pathways for CPM and bile acid amides are shown to be independent. By contrast, although CPM ex cretion was markedly inhibited by organic an 30 Takikawa/Uehida/Sano/Yamanaka Biliary Cefpiramidc Excretion ions and bile acid sulfates and glucuronides, the inhibitory effect of CPM on the biliary excretion of these compounds was shown to be minor. CPM is sometimes used for the treatment of biliary tract infection since its biliary delivery rate is very high among P-lactam antibiotics.…”
Section: Discussionmentioning
confidence: 83%
“…6B). Formation of CDC-gl was also confirmed by negative-ion fast-atom bombardment-mass spectrometry analysis of the bile according to the presence of m/z 567 and m/z 589, [M-HI-of dihydroxy bile acid glucuronide and its sodium salt, respectively, as previously reported (26,27). Table 2 summarizes the conjugation of [ 14C]CDC in the bile.…”
Section: Resultsmentioning
confidence: 92%
“…[ 14 C]Taurocholate and [ 14 C]CA were infused at the rate of 1.0 mmol/min/100 g for 90 min. 21,22 [ 14 C]TUDC was infused at the rate of 1.0 and 2.0 mmol/min/100 g for 90 min according to the finding of Kitani and Kanai that the biliary excretory maximum of TUDC is twice as high as that of TC. 23 Furthermore, the effect of [ 14 C]TUDC, which was simultaneously infused at the rate of 1.0 mmol/min/100 g, on the biliary excretion of [ 3 H]TC, which was infused at the rate of 1.0 mmol/min/ 100 g for 90 min after the colchicine treatment, was studied.…”
Section: Methodsmentioning
confidence: 99%